Patient With Unresectable Cholangiocarcinoma Treated With Radiofrequency Hyperthermia in Combination With Chemotherapy: A Case Report. (June 2018) - Ryu, Juyoung; Lee, Kangwook; Joe, Changmug; Joo, JongCheon; Lee, Namhun; Yoo, Hwa-Seung
Hyperthermia, which is a noninvasive treatment that causes tumor cells to become heated and that works in synergy with anticancer drugs and radiation therapy, is emerging as a promising treatment for patients with cancer. The purpose of this study is to report the efficacy of hyperthermia combined with chemotherapy (gemcitabine/cisplatin) for the treatment of a patient with unresectable cholangiocarcinoma. A 54-year-old man was diagnosed as hilar cholangiocarcinoma (Klatskin tumor) and was administered neoadjuvant and preoperative radiation with chemotherapy. However, because the treatment with radiation and chemotherapy was not successful, he decided to undergo hyperthermia combined with chemotherapy as a second treatment option. He was suffering from fatigue, dyspepsia, epigastralgia, and jaundice. Hyperthermia combined with chemotherapy was administered 32 times over a period of 4 months. The patient experienced no critical complications, and the patient's condition improved, with the carbohydrate antigen 19-9 (CA 19-9) and the total bilirubin levels being relatively lowered. In addition, the computed tomography scan showed that the cholangiocarcinoma had not progressed. In conclusion, this case report suggests radiofrequency hyperthermia combined with chemotherapy may be a promising treatment option for patients with unresectable cholangiocarcinoma.